Identity-affirming religious experience and political activism among LGBT people - Cravens, Royal G. (Journal of contemporary religion, 2021)
Contrary to stereotypes, recent research indicates that a majority of LGBT people identify as religious. As with heterosexuals, religious belief and activity conditionally act as political resources among LGBT people, augmenting political participation. In recent decades, an increasing number of religious congregations have adopted theologies that explicitly affirm their LGBT congregants’ identities. In this study, I quantitatively examine affirming religious experiences, using data collected from a unique survey instrument administered to a sample of LGBT adults in the United States. Building on the resource paradigm of political participation, I hypothesize that attending an affirming religious congregation increases psychological resources such as LGBT group consciousness and internal efficacy that are easily translatable into political participation among marginalized groups. I find that about two in ten LGBT people report attending an affirming congregation and that attendance is positively associated with both psychological resources and political participation across a number of indicators, including volunteerism, financial contributions, and voting.